Analisis Pesan Moral Pada Sinetron Cinta Setelah Cinta - Muhammad Rangga Saputra; Anang Walian; Suryati Suryati (Jurnal Ilmu Komunikasi Dan Media Sosial (JKOMDIS), 2023)
This thesis is entitled "Analysis of Moral Messages in the Soap Opera Cinta After Cinta" in the current technological era, television is no stranger to society, television functions as a medium and means of information and entertainment and one of them is soap operas. In general, soap operas depict stories of everyday life for the community. There is a moral message contained in films/shows. Morals are good and bad teachings that apply to society. The purpose of this study is to find out what moral messages are contained in the soap opera Cinta After Cinta. This study uses Charles Sanders Peirce's semiotic analysis and uses qualitative research in the form of observation and documentation. The documentation method takes several scenes from the soap opera Cinta After Cinta which was broadcast on 16 May-20 May 2022. The results of this study contained a moral message that was conveyed in the broadcast on 16 May-20 May 2022. Among other things, wise parents are to always protect their children, promises marriage is not just a promise but must be kept, caring for a husband is the duty of a wife, a dutiful child is helping and praying for his parents and others.